Determinasi Pada Loyalitas Pengaruh Kualitas Pelayanan dan Persepsi Harga Melalui Kepuasan - Khilyatin Ikhsani; Agung Hudaya (Jurnal Informatika Ekonomi Bisnis, 2023)
Micro enterprises are believed to be able to thrive in unstable situations because they operate independently and have a relatively small scope. Small and medium-sized business owners must be able to survive in an industry dominated by large and medium-sized companies. To achieve this, they need effective marketing strategies, focusing on service quality and price perception, in order to create customer satisfaction and loyalty. The sustainability of micro and small business owners depends on how well their products can endure. In this study, the third key factor (TKT 3) is active research and development. This may involve analytical studies and laboratory research to physically validate analytical predictions about separate elements of technology. For instance, it could relate to components that have not yet been integrated or those that represent a sample. The study population consists of residents in Tangsel, and sampling is done using purposive techniques. Using the Hair formula, the sample size is rounded to 100 individuals who will serve as research respondents. These respondents will be provided with a Google Form questionnaire for the research.